The Common Good and the Orientation toward Christ - Hooton, Peter (International journal of public theology, 2021)
Abstract The common good is a surprisingly elusive concept. While we may reasonably assume it to describe a life of shared purpose and solidarity in ordered, just, and equitable community, there is, unsurprisingly, no one agreed description of the shape and structure of such a life – which is why those who write about the common good often prioritize the quality of the conversation over the substance of the vision. This article holds the notion of the common good, for all its imprecision, to be nonetheless importantly, and demonstrably, more than the sum of its variously described parts. It explores some historical and contemporary understandings of the common good before proposing an holistic and essentially Christological approach, rooted in a responsible and participatory account of being drawn principally from Dietrich Bonhoeffer’s theology.